Publication Trend of R&D in the Journal of Biological Education in Indonesia (Sinta 2: 2017-2021): A Systematic Literature Review - Abdulkadir Rahardjanto; Husamah Husamah (IKIP Mataram, 2022)
Research on R&D in education is still very much needed. This systematic literature review (SLR) was aimed to analyze the trend of publications in the field of R&D in the journal of biological education in Indonesia. The results of this SLR will illustrate the condition of R&D publications until 2021, both in terms of quantity, quality, and contribution. This systematic literature review adopts five-step guidelines from Denyer and Tranfield. Based on the study results, it can be seen that journals in the field of biology education have published a total of 379. JPBI has published the most articles, as many as 206 articles. Specifically, in the field of R&D, JPBI has published 37 articles on R&D. This shows a good contribution to the development of science and technology, especially in terms of products produced by R&D. There are 9 models used, and the dominant ones used are 3D Thiagarajan, ADDIE, and Borg & Gall. In general, 61% of articles do not consistently carry out the stages of the R&D model used. The dominant keyword used is